Role of International Actors in Human Rights Issues in Iran from 1990-2008 - Fard, Hassan Davoodi (2010)
This thesis seeks to explore the role of international human rights actors related to promoting of human rights values in Iran from 1990-2008. The Islamic Republic of Iran‟s discourse and practice on human rights issues has raised much criticism in national and international levels. While Iranian government has had its own human rights perspective in treating its citizens, many international human rights organizations have campaigned to influence the behaviour of Iranian government and people in terms of development of human rights values in Iran. This study departs from the Universal, Cultural Relativism, and Islamic perspective of human rights and defends the Universal perspective of human rights in general. The study, as a qualitative study, is based on Constructivism theory to determine the role of human rights actors on Iranian government and people. To illustrate the interaction and relationship between human rights actors and Iranian state(Government and People) the thesis relies on conceptual framework captured by Constructivism theory. It focuses on the role of international human rights actors such as European Union, and international nongovernmental organizations such as Amnesty International and Human Rights Watch, and domestic nongovernmental organizations involved in promoting human rights in Iran. It seeks to find the influence of these actors on the behaviour of Iranian state regarding human rights. This study aims to find if these international actors are changing the features of human rights in Islamic Republic of Iran, and show how Iranian government and people deal with both international and national actors active in promoting human rights values. The findings of this study demonstrate that human right actors have played a significant role in the human rights situation in Iran. It also shows that the Iranian government and society have been affected by efforts of human rights actors after 1990. In addition, this study reveals that the emergence of Non Governmental Organizations of human rights in Iran is the outcome of the influence of international human rights actors on both the Iranian government and society. And finally, this study argues that the human rights actors – both domestic and international – are challenging the Iranian government behaviour related to human rights issues. Accordingly, the acceptance of the universality of human rights is inevitable for Iranian government in the future.